An Exploratory Randomized Trial of Physical Therapy for the Treatment of Chemotherapy-Induced Peripheral Neuropathy. (March 2020) - Andersen Hammond, Elizabeth; Pitz, Marshall; Steinfeld, Karen; Lambert, Pascal; Shay, Barbara
Background . Chemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of taxane treatment and cannot currently be prevented or adequately treated. Physical therapy is often used for neural rehabilitation following injury but has not been evaluated in this patient population. Methods . Single-blind, randomized controlled exploratory study compared standard care to a physical therapy home program (4 visits) throughout adjuvant taxane chemotherapy for stage I-III patients with breast cancer (n = 48). Patient questionnaires and quantitative sensory testing evaluated the treatment effect throughout chemotherapy to 6 months post treatment. Nonrandomized subgroup analysis observed effect of general exercise on sensory preservation comparing those reporting moderate exercise throughout chemotherapy to those that did not exercise regularly. Clinical Trial Registration . clinicaltrials.gov (NCT02239601). Results . The treatment group showed strong trends toward less pain (odds ratio [OR] 0.41, 95% confidence interval [CI] 0.17-1.01; P = .053) and pain decreased over time (OR 0.85, 95% CI 0.76-0.94; P = .002). Pain pressure thresholds ( P = .034) and grip dynamometry ( P < .001) were improved in the treatment group. For the nonrandomized subgroup analysis, participants reporting general exercise had preservation of vibration (Left P = .001, Right P = .001) and normal heat pain thresholds (Left P = .021, Right P = .039) compared with more sedentary participants. Conclusion . Physical therapy home program may improve CIPN pain in the upper extremity for patients with breast cancer, and general exercise throughout chemotherapy treatment was observed to have correlated to preservation of sensory function. Further research is required to confirm the impact of a physical therapy home program on CIPN symptoms.